Tuberculosis in 0-5-year-old children following TB contact investigations: a retrospective study in a low burden setting - Cassandre Pasqualini; Laure Cohen; Enora Le Roux; Enora Le Roux; Marion Caseris; Albert Faye; Albert Faye; Albert Faye (Frontiers Media S.A., 2023)
IntroductionWe assessed the risk of tuberculosis (TB), the management and the outcomes of 0-5-year-old children after TB contact investigations in a low-burden setting.MethodAll 0-5-year-old children who attended the TB clinic of Robert Debre Hospital, Paris, France, for a TB contact investigation between June 2016 and December 2019 were included in this retrospective study. The risk factors for TB were assessed using univariate and multivariate analyses.ResultsA total of 261 children were included. Forty-six (18%) had TB, including 37 latent tuberculosis infections (LTBIs) and 9 active TB diseases. The prevalence of TB was 21% among high-risk contacts, i.e., household or close contacts and regular or casual contacts. There was no TB among intermediate- or low-risk contacts (0/42). Living under the same roof with (OR: 19.8; 95% CI: 2.6-153), the BCG vaccine (OR: 3.2; 95% CI: 1.2-8.3), contact duration >40 h (OR: 7.6; 95% CI: 2.3-25.3) and sleeping in the room of the index case (OR: 3.9; 95% CI: 1.3-11.7) were independently associated with TB. The BCG vaccine was no longer associated when the analysis was restricted to interferon gamma release assay results. Among children without initial LTBI, antibiotic prophylaxis was not prescribed for 2-5-year-old children or for 32/36 (89%) of 0-2-year-old children who had intermediate- or low-risk contact. Overall, none of these children experienced TB.ConclusionIn our low prevalence setting, the risk of TB in 0-5-year-old children following a household or close contact was high. Further studies are needed to better assess prophylaxis recommendations in intermediate or low risk contact.